Clinical Pharmacist-Led Collaboration of Multiple Clinical Professions Model Focusing on Continuity of Pharmacotherapy: Japanese Version of the Lund Integrated Medicines Management (LIMM) Model - Rie Sato; Syuichi Aoshima; Tommy Eriksson (Pharmacy)
(1) Background: In general, it is known that continuity of care can contribute to an increase in patient satisfaction, reduce health care costs, and improve patient outcomes. A guarantee of continuity in pharmacotherapy is a big challenge facing Japanese health care as a system that encourages cooperation/collaboration for pharmacists with other health care professions is currently lacking. (2) Method: This is a narrative review. (3) Results: The Lund Integrated Medicine Management (LIMM) model describes a systematic approach to individuals and was developed in Sweden to optimize pharmacotherapy among elderly inpatients. The aim of the LIMM model is to provide patients with continuous pharmacotherapy at different levels of care. The LIMM model, in which a clinical pharmacist is the catalyst and leads other health care professions in completing the process, has the potential to reduce potentially inappropriate prescriptions, reduce rehospitalization risk, unscheduled hospital revisits due to problems related to medications, reduce total medical expenditure, and provide a comprehensive understanding of patients’ conditions of taking medicine. (4) Conclusions: Introducing a framework such as Sweden’s LIMM model, anchored by clinical pharmacists, could provide a good opportunity to promote collaborations among different health care professionals and improve continuity in pharmacotherapy.